Analisis Unsur Intrinsik dan Ekstrinsik dalam Cerita Rakyat Suri Ikun dan Bui Ikun pada Masyarakat Belu - Destin Agustina Ndolu; Marselus Robot; Margareta P. E. Djokaho (YASIN, 2026)
Although folklore plays an important role in preserving cultural, moral, and educational values, studies comprehensively examining the intrinsic and extrinsic elements of the folktale Suri Ikun dan Bui Ikun remain limited. This study aimed to describe the intrinsic and extrinsic elements of the folktale Suri Ikun dan Bui Ikun among the Belu community. This study employed a qualitative descriptive method with a structural approach. The research data consisted of phrases, sentences, and paragraphs from the story Suri Ikun dan Bui Ikun, published in the 2014 book Cerita Rakyat Nusa Tenggara Timur Sekolah Dasar Kelas V. The data were collected through a literature review and analyzed qualitatively and descriptively. The findings showed that the story’s intrinsic elements included the themes of kinship and affection, a chronological plot, characters and characterization, setting, a third-person point of view, personification, and moral messages concerning the importance of kinship, responsibility, and loyalty within the family. Its extrinsic elements reflected the life of the Belu Regency community, which highly values kinship, customary law, mutual cooperation, and harmonious relationships with nature. This story also represents the cultural identity of the Belu community and serves as a medium for transmitting cultural values to younger generations. This study concludes that Suri Ikun dan Bui Ikun contains cultural, moral, and educational values that contribute to understanding the identity of the Belu community and preserving regional literature.